Determinants of Women's Decision-Making Power in Pest and Disease Management: Evidence From Uganda - Okonya, J.; Mudege, Netsayi N.; Nyaga, J.N.; Jogo, W. (Frontiers Media, 2021)
Using quantitative data from a household survey carried out in Rubanda district, Southwestern Uganda among smallholder farmers of potato, this paper examines determinants of intra-household decision-making of women in relation to pest and disease management in a cropping season. Pests and diseases cause significant crop losses and contribute to household food insecurity in most of sub-Saharan Africa. Their management is therefore key in enhancing food security. While there are many pest and disease management practises, little is known about women's autonomy in decision-making on this topic. The survey collected quantitative data from 260 households (130 men and 130 women). To get a more accurate proxy for decision-making power, a weighted index and linear regression models were used to examine the relationship between decision-making power of women in pest and disease management and socio-demographic characteristics. We found that farming experience, use of hired labour and membership to a farmers group, were positively associated with woman's autonomy in decision-making during pest and disease management. Our data also show that higher levels of education, farm income and age consistently improve women authority. The implications of the study are that, women should equally be targeted during pest and disease management interventions such as training.